Carotid endarterectomy for symptomatic carotid stenosis - Saritphat Orrapin (2018)
© 2017 The Cochrane Collaboration. Published by John Wiley & Sons, Ltd. Background: Stroke is the third leading cause of death and the most common cause of long-term disability. Severe narrowing (stenosis) of the carotid artery is an important cause of stroke. Surgical treatment (carotid endarterectomy) may reduce the risk of stroke, but carries a risk of operative complications. This is an update of the Cochrane Review, originally published in 1999, and most recently updated in 2011. Objectives: To determine the balance of benefit versus risk of endarterectomy plus best medical management compared with best medical management alone, in people with a recent symptomatic carotid stenosis (i.e. transient ischaemic attack (TIA) or non-disabling stroke). Search methods: We searched the Cochrane Stroke Group Trials Register (last searched in July 2016), CENTRAL (2016, Issue 7), MEDLINE (1966 to July 2016), Embase (1990 to July 2016), Web of Science Core Collection, ClinicalTrials.gov, WHO International Clinical Trials Registry Platform (ICTRP) portal, and handsearched relevant journals and reference lists. Selection criteria: We included randomised controlled trials. Data collection and analysis: Two review authors independently selected studies, assessed risk of bias, and extracted the data. Main results: We included three trials involving 6343 participants. As the trials differed in the methods of measurement of carotid stenosis and in the definition of stroke, we did a pooled analysis of individual patient data on 6092 participants (35,000 patient years of follow-up), after reassessing the carotid angiograms and outcomes from all three trials using the primary electronic data files, and redefined outcome events where necessary, to achieve comparability. On re-analysis, there were no significant differences between the trials in the risks of any of the main outcomes in either of the treatment groups, or in the effects of surgery. Surgery increased the five-year risk of ipsilateral ischaemic stroke in participants with less than 30% stenosis (N = 1746, risk ratio (RR) 1.27, 95% confidence interval (CI) 0.80 to 2.01), had no significant effect in participants with 30% to 49% stenosis (N = 1429, RR 0.93, 95%CI 0.62 to 1.38), was of benefit in participants with 50% to 69% stenosis (N = 1549, RR 0.84, 95%CI 0.60 to 1.18), and was highly beneficial in participants with 70% to 99% stenosis without near-occlusion (N = 1095, RR 0.47, 95%CI 0.25 to 0.88). However, there was no evidence of benefit (N = 271, RR 1.03, 95%CI 0.57 to 1.84) in participants with near-occlusions. Ipsilateral ischaemic stroke describes insufficient blood flow to the cerebral hemisphere, secondary to same side severe stenosis of the internal carotid artery. Authors' conclusions: Endarterectomy was of some benefit for participants with 50% to 69% symptomatic stenosis (moderate-quality evidence), and highly beneficial for those with 70% to 99% stenosis without near-occlusion (moderate-quality evidence). We found no benefit in people with carotid near-occlusion (high-quality evidence).